Shareholder Voice and the Market for Corporate Control - Peter V. Letsou (Washington University Law Quarterly, 1992)
Part I examines in greater detail the role of shareholders in public corporations. Part II critiques existing explanations for rules that limit shareholder power over business decisions. Part III presents an alternative explanation for the limitations on shareholder power to control business decisions based upon the link between shareholder voice in management, on the one hand, and the efficient operation of the market for corporate control and organized securities exchanges, on the other.
Keywords: Stockholders